1996
DOI: 10.1097/00000658-199609000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Re-Engineering Ventilatory Support to Decrease Days and Improve Resource Utilization

Abstract: ObjectiveThe objective of this study was to describe the development of a cost-effective ventilatory strategy using a portable microprocessor-controlled respiratory monitor (Bicore CP-1 00; Allied Healthcare Products, Riverside, CA). Summary Background DataUntil recently, clinicians have had to accept the uncertainties of clinical judgment, which unfortunately, often biased the patient to a prolonged ventilatory course to avoid extubation failures, necessitating reintubation. MethodsOver a 4-year period, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In another study, an approach akin to an open-loop PSV system was employed, in which the response or input variable was WOB per breath, directly measured with an esophageal balloon catheter, and the output variable was PSV. 2 The clinicians maintained WOB per breath in a specific and fairly normal physiologic range by increasing or decreasing PSV as needed. When WOB per breath was maintained in that range with PSV, adults weaned faster than with the traditional method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, an approach akin to an open-loop PSV system was employed, in which the response or input variable was WOB per breath, directly measured with an esophageal balloon catheter, and the output variable was PSV. 2 The clinicians maintained WOB per breath in a specific and fairly normal physiologic range by increasing or decreasing PSV as needed. When WOB per breath was maintained in that range with PSV, adults weaned faster than with the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…In adults treated with PSV it was found that WOB of 2-8 J/min was well tolerated. 3 Another clinical study 2 reported that WOB maintained in a fairly normal range during PSV was well tolerated. Our PSV advisory system's target f and V T ranges are congruent with those applied to spontaneously breathing adults receiving PSV: 10 -25 breaths/min, and 6 -8 mL/ kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have found WOB to be a sensitive method of predicting successful weaning and extubation [57] although others have not been able to confirm this [58]. Differentiating the WOB into its components has revealed that in certain circumstances imposed WOB may be the most significant factor increasing total WOB such that patients benefit from discontinuation of respiratory support [59].…”
Section: Work Of Breathingmentioning
confidence: 99%